Colonization of Mice With Amoxicillin-Associated Klebsiella variicola Drives Inflammation via Th1 Induction and Treg Inhibition - Lin, Huai; Wang, Qing; Liu, Lei; Chen, Zeyou; Das, Ranjit; Zhao, Yanhui; Mao, Daqing; Luo, Yi (Frontiers in Microbiology, 2020)
β-Lactam antibiotics can increase the resistance and virulence of individual intestinal microorganisms, which may affect host physiology and health. Klebsiella, a crucial gut inhabitant, has been confirmed to be resistant to most β-lactam antibiotics and contributes to the etiology of inflammatory bowel disease (IBD). In this study, the influence of amoxicillin (AMO) on Klebsiella and its role in colitis was investigated in an antibiotic cocktail (ABx) murine model. The results suggested that a seven-day amoxicillin treatment significantly enriched the abundance of Klebsiella and enhanced serum resistance, antibiotic resistance, and biofilm formation ability of Klebsiella variicola (K. variicola) compared to the wild-type strain in the control group mice. Colonization of mice with the AMO- associated K. variicola could induce Th1 cells and inhibit Treg differentiation to promote inflammation in ABx murine model. In addition, inoculation of AMO- associated K. variicola in dextran sodium sulfate (DSS)-induced colitis murine model mice also confirmed that K. variicola colonization exacerbated inflammation as assessed by increased TNF-α, IFN-γ, IL-17a, and disease activity (DAI) levels; decreased colon length and bodyweight; and a disrupted Th1/Treg balance. The results of our study demonstrate that amoxicillin enhances Klebsiella virulence in mice by disrupting the T cell equilibrium to exacerbate colitis, thereby providing a reference for proper antibiotic prescription.